Ответ: вектор р = ( 0; 2 ; 10 ) , а вектор n = ( - 2 ; 1 ; - 1 ) .
Пошаговое объяснение: Вектор p = ( 2 ; 0 ; 6 ) + 2 ( - 1 ; 1 ; 2 ) =
= ( 2 ; 0 ; 6 ) + ( -2 ; 2 ;4 ) = ( 0 ; 2 ; 10 ) ;
n = ( - 1 ; 1 ; 2 ) - 0,5 ( 2 ; 0 ; 6 ) = ( - 1 ; 1 ; 2 ) - ( 1 ; 0 ; 3 ) = ( - 2 ; 1 ; -1 ) .
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ: вектор р = ( 0; 2 ; 10 ) , а вектор n = ( - 2 ; 1 ; - 1 ) .
Пошаговое объяснение: Вектор p = ( 2 ; 0 ; 6 ) + 2 ( - 1 ; 1 ; 2 ) =
= ( 2 ; 0 ; 6 ) + ( -2 ; 2 ;4 ) = ( 0 ; 2 ; 10 ) ;
n = ( - 1 ; 1 ; 2 ) - 0,5 ( 2 ; 0 ; 6 ) = ( - 1 ; 1 ; 2 ) - ( 1 ; 0 ; 3 ) = ( - 2 ; 1 ; -1 ) .